Comparison Calculation Thick Pavement Rigid (Rigid Pavement) Between Method Manual Design Pavement Road (Revision 2017) With Method Build Clan Pd-T-14-2003, on Ruas Road Shell Until Limit City Land Grogot East Kalimantan - Muhammad Gunawan Prime (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Roads are a means of transportation for supports various development sector and is a means of regional development of areas along the road the. By Because That, system transportation road kingdom is activity mover economy Which important beside Also become means activity resident Which involve problems economy, social And culture. Development road intended For make it easier connection from something regions to other regions, as well as to develop the economic potential that exists in area the. Objective from study this is For Plan Thick Construction Pavement Rigid With Manual Methods of Pavement Design Road 2017 and Methods Pd T- 14-2003 and compare both methods the. The thickness of the concrete slab obtained from the 2017 Road Pavement Manual method is of 28.5 cm with a thin concrete layer of 10 cm and a drainage layer with a thickness of 15 cm. The thickness of the concrete slab obtained from the Pd T-14-2003 method which is 18 cm. Based on the reinforcement calculation As Min > As Required then obtained reinforcement Which efficient For thick plate concrete 180 mmm is reinforcement 10 mm in diameter with a distance of 300 transverse and longitudinal reinforcement mm, transverse connection (Dowel) is required Ø 28 mm, with a length (L) of 450 mm and the distance (s) between dowels is 300 mm, while the longitudinal connection (Tie Bar) that is with Ø 16 mmm with long 700 mmm And distance 60 mmm. As well as Based on the calculation of reinforcement As Min > As Required, the reinforcement obtained is efficient for a concrete plate thickness of 265 mm is reinforcement with a diameter of 12 mm with distance between transverse reinforcement and longitudinal reinforcement 300 mm, transverse connection (Dowel) required Ø 32 mm, with a length (L) of 450 mm and a distance (s) between dowel 300 mmm, while the longitudinal connection (Tie Bar) is with Ø 16 mm with a length of 700 mm and a distance of 60 mm. Based on the comparison description calculation of rigid pavement thickness using the Manual Design Method Pavement Road (Revision 2017) with thick pavement rigid (rigid pavement) with Method Build Clan Pd T-14-2003 For use method MDPJ 2017 show will more thick compared to method PD Q 14 Year 2003.